2012
DOI: 10.1007/s10965-012-9867-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance evaluation of poly (ether-imide) incorporated polysulfone hemodialysis membranes

Abstract: Biocompatible Polysulfone (PSf) hemodialysis membranes were prepared by phase inversion technique using poly (ether-imide) (PEI) as the modification agent and Polyethylene glycol (PEG-200) as the pore former. The effect of PSf/PEI blend ratio on the morphology, hydrophilicity, water content, porosity, glass transition temperature, mechanical strength, biocompatibility and permeation rate of the prepared membranes were studied and were found to be improved significantly by the incorporation of PEI in the dope s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Barzin and Sadatnia have shown that delayed demixing results in a spongy structure . The presence of the hydrophilic additives improved the water tolerance of the casting solution and hence the solvent outflux rate decreased significantly on the glass‐contacting (bottom) surface . However, membranes cast on the nonwoven fabric do not show this characteristic (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Barzin and Sadatnia have shown that delayed demixing results in a spongy structure . The presence of the hydrophilic additives improved the water tolerance of the casting solution and hence the solvent outflux rate decreased significantly on the glass‐contacting (bottom) surface . However, membranes cast on the nonwoven fabric do not show this characteristic (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Due to modifications where hydrophilic groups are introduced onto the membrane surface, a sharp decline has been observed by other researchers [52][53][54] . Further, it was explained that the protein adsorption on hydrophilic surfaces occurred in one of the two modes.…”
Section: Protein Adsorptionmentioning
confidence: 91%
“…Therefore benchmark PSf flat sheet (home-made) membrane was prepared based on a conventional membrane prepared via phase inversion method [12,14,39,40].…”
Section: Methodsmentioning
confidence: 99%